Sub-1 mL sample requirement for simultaneous determination of 17 organic and inorganic anions and cations in Antarctic ice core samples by dual capillary ion chromatography - Sanz Rodriguez, E; Plummer, C; Nation, M; Moy, A; Curran, M; Haddad, PR; Paull, B (Analytica Chimica Acta, 2019)
The significant advance of delivering high value multi-species data from sub-1 mL ice core sample volumes allows higher temporal resolution in deposition records of inorganic and low molecular weight organic anions and cations. The determination of these species is a fundamental strategic requirement in modern paleoclimate studies. Herein, for the first time, a dual capillary ion chromatography (Cap-IC) based method for the simultaneous separation of 17 organic and inorganic anions and cations in low volume Antarctic ice core samples is presented. The total amount of sample required for direct injection has been reduced to 190 μL, which is 35 times lower than the amount of sample required by standard ion chromatography methods. A dual Cap-IC system configured for the simultaneous determination of cations and anions was used throughout. A range of chromatographic parameters was optimised for both anion and cation systems to obtain baseline separations of all target analytes in a suitable run time and to minimise the amount of sample required. Baseline separation of matrix and trace marker ions were achieved in less than 35 min, after injecting only 40 μL of sample in each IC system. Limits of detection (LODs) for all analytes determined were within a range similar to that achieved by previously published standard bore IC-based methods. Intra- and inter-day repeatability were evaluated, with both parameters being typically below 3% for peak area. In further validation of the method, a comparative analysis of a set of 420 ice core samples from Aurora Basin North site, Antarctica, previously analysed by standard IC, established that the proposed low sample volume technique was applicable as a routine measurement approach in ice core analysis projects.